Vestibular paroxysmia: Long-term clinical outcome after treatment - Chen, Chih-Chung; Lee, Ting-Yi; Lee, Hsun-Hua; Kuo, Yu-Hung; Bery, Anand K.; Chang, Tzu-Pu (Frontiers in Neurology, 2022)
Objective: To study the long-term treatment outcome of vestibular paroxysmia (VP) Study Design: Retrospective study Setting: Tertiary referral hospital Methods: We analyzed records of 29 consecutive patients who were diagnosed with VP and who were treated with VP-specific anticonvulsants for at least 3 months. Patients were followed for a minimum of 6 months. We recorded and assessed starting and target dosage of medications, time to achieve adequate therapeutic response, adverse effects and the rates of short-term and long-term remission without medication. Results: All 29 patients were started on oxcarbazepine as first-line treatment, and 93.1% and 100% of patients reported good-to-excellent therapeutic response within 2 and 4 weeks, respectively. Three patients switched to other anticonvulsants at 3 months. At long-term follow-up (8 - 56 months), most (84.6%) oxcarbazepine-treated patients maintained good therapeutic response at doses between 300 and 600 mg/day. Eleven (37.9%) patients experienced complete remission without medication for more than one month, of which six (20.7%) had long-term remission off medication for more than 12 months. Nineteen (65.5%) patients had neurovascular compression of vestibulocochlear nerve on MRI, but its presence or absence did not predict treatment response or remission. Conclusion: Low-dose oxcarbazepine monotherapy for VP is effective over the long term and is generally well-tolerated. About 20% of patients with VP in our study had long-term remission off medication.